(untitled) (Universal International Scientific Journal, 2026)
This article is a theoretical study of the concept of family and its representation in the imagination of Uzbek and Kyrgyz girls from a national-psychological perspective. The results of a socio-psychological survey conducted to determine the ethnopsychological characteristics of family values ​​are also analyzed.